001 BP: USING PHOTOGRAPHY IN PHENOMENOLOGICAL RESEARCH IN THE CONTEXT OF CHRONIC ILLNESS AND DISABILITY: A REFLECTIVE OVERVIEW. (3rd March 2017) - Williamson, I; Papaloukas, P; Quincey, K; Lond, B; Akhtar, Y
Abstract : As qualitative health researchers are increasingly recognising the limitations of one-off interviews for accessing the 'lifeworld' of participants, and the taking and sharing of photographs to document aspects of day to day life has become a quotidian (but arguably mundane) habit for many, so research integrating a photographic component is flourishing. In this presentation we reflect on our experiences of integrating participant-authored photographs with semi-structured interviews within an interpretative phenomenological approach. As critical health psychologists our focus has been on aiming to give an 'authentic' voice to individuals and communities who might be considered marginalised or hard-to-reach. Thus, we illustrate our arguments using examples from a series of recent research projects which have looked at LGBT people living with multiple sclerosis, men with breast cancer, mothers of daughters with Rett syndrome and partners of individuals with acquired brain injury. We discuss how participants found taking the photographs, the barriers some participants faced and how we tried to overcome these. We reflect on the nature of the photographs taken and discuss various strategies for integration with the interview component for synergistic results. We consider methodological, epistemological and ethical aspects with a particular focus on concerns around 'methodolatry'. In the final part of the presentation we explore the challenges of interpretation using two examples – " gym bathroom " from the MS study, and "c loud " from the men with breast cancer study. We conclude with some thoughts about what collaboration should mean in relation to research using photography in this field of research activity.